Climate-induced liquidity crises: interbank exposures and macroprudential implications - Paola D'Orazio; Jessica Reale; Anh Duy Pham (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2023)
Although climate-induced liquidity risks can cause significant disruptions and instabilities in the financial sector, they are frequently overlooked in current debates and policy discussions. This paper proposes a macro-financial agent-based integrated assessment model to investigate the transmission channels of climate risks to financial instability and study the emergence of liquidity crises through interbank market dynamics. Our simulations show that the financial system could experience serious funding and market liquidity shortages due to climate-induced liquidity crises. Our investigation contributes to our understanding of the impact - and possible solutions - to climate-induced liquidity crises, besides the issue of asset stranding related to transition risks usually considered in the existing studies.
Keywords: 330; Agent-Based Modeling; Climate Risks; Prudential Regulation; Interbank Market; Liquidity Crises